Application of the Scale for Assessment and Rating of Ataxia in toddlers. (September 2022) - Schouwstra, K.J.; Polet, S.S.; Hbrahimgel, S.; Tadema, A.S.; Burgerhof, J.G.M.; Brandsma, R.; Sival, D.A.
Abstract: Introduction: In young children with early onset ataxia (EOA), quantitative rating of ataxia by the Scale for Assessment and Rating of Ataxia (SARA) is longitudinally influenced by the physiological age effect on motor coordination. To enable longitudinal quantitative interpretation of ataxia by SARA in children with EOA, the EPNS ataxia working group has previously determined SARA-scores in typically developing children (4–16 years of age). In toddlers, this information is still lacking. We therefore aimed to investigate the feasibility and reliability of SARA-scores in typically developing toddlers. Methods: In 57 typically developing toddlers (2–4 years), we aimed to determine the: 1. feasibility of SARA-scores, 2. age-related pre-requisites to obtain SARA-scores in toddlers over all domains, 3. SARA-score reliability, 4. mathematical age connection of SARA-scores in toddlers and older children. Results: In typically developing toddlers, the feasibility of SARA is strongly age-dependent ( p  < .000). After computing compensations for two age-related, unfeasible and therefore un-assessable kinetic subtasks and after allowing the videotaping of non-kinetic SARA sub-task performances at home, the SARA was fully reliably assessable in all (n = 57) toddlers (ICC = 0.732). From two to 16 years of age, SARA-scores were mathematically represented by one continuous, exponentially decreasing trend line approaching the adult-optimum at 16 years of age. Conclusion: In toddlers, SARA-scores are reliably assessable, by using two age-compensations and allowing the videotaping of SARA-performances partly at home. In children with EOA, these data enable longitudinal quantification and interpretation of quantitative ataxia-scores by SARA from 2 years of age throughout childhood. Highlights: SARA-scores in typically developing toddlers: Are influenced by age. Are fully feasible after applying two numerical age-compensations. Can partly be obtained from home-videos. Are reliably assessable (substantial ICC). Reflect an exponentially declining trend-line continuing throughout childhood.